„In wen der gleiche Funke schlug…“. Wissen und Visionen. Theorie und Politik der Ökonomen im Stefan George-Kreis 1918-1933 - Schönhärl, Korinna (Forschung Frankfurt)

Sprachbildlichkeit und Musikalität. Zur ästhetischen Erfahrung bei Klopstock - van Laak, Lothar (Wort und Schrift: Das Werk von F. G. Klopstock)

Literarische und filmische Anthropologie: Patrick Süskinds Roman ‘Das Parfum’ in der Verfilmung durch Tom Tykwer und Bernd Eichinger. - van Laak, Lothar (Gegenwartsliteratur. Ein germanistisches Jahrbuch/A German Studies Yearbook 7/2008)

Klopstock zwischen Antike u. Moderne. "Klassische" Vorbilder u. Selbstkanonisierung - Elit, Stefan (Akten des XI. Germanistenkongresses der IVG. Paris 2005. "Germanistik im Konflikt der Kulturen" (Jahrbuch für Internationale Germanistik. A: Kongressberichte 87))

Der späte Klopstock und Johann Heinrich Voß. Ein Spannungsverhältnis, poetologisch betrachtet - Elit, Stefan (Wort und Schrift – Das Werk von F. G. Klopstock (Hallesche Forschungen 27))

Schulkultur als Kontext naturwissenschaftlichen Lernens. Allgemeine und fachspezifische explorative Analysen - van Ackeren, Isabell; Block, Rainer; Kullmann, Harry; Sprütten, Frank; Klemm, Klaus (Zeitschrift für Pädagogik)
Keywords: Lernen; Schulkultur

Zu: Leitbild mit Widersprüchen. Vormärz und Aufklärung Internationales Symposium. 10.-12. Mai 2007 (ausgerichtet vom Forum Vormärz Forschung in Zusammenarbeit mit der Bundesakademie für kulturelle Bildung in Wolfenbüttel) - Elit, Stefan (Zeitschrift für Germanistik Neue Folge)

„Ein Mann von Feuer und Talenten“. Leben und Werk von Carl Friedrich Cramer, hg. v. Rüdiger Schütt, Göttingen 2005 (Grenzgänge. Studien zur skandinavisch-deutschen Literaturgeschichte 5) - Elit, Stefan (JbIG 40, H. 2 (Jahrbuch für brandenburgische Landesgeschichte))

Jürgen Hebel: Hölty. Melancholie und poetische Existenz, Münster 2006 (facies nigra. Studien zur Melancholie in Kunst und Literatur 3) - Elit, Stefan (JbIG 40, H. 1 (Jahrbuch für brandenburgische Landesgeschichte))

Tausch/Gaben. Ökonomische und anökonomische Logik in ‚Flore und Blanscheflur‘ und ‚Apollonius von Tyrland' - Egidi, Margreth

„Schrift und ‚ökonomische Logik‘ im höfischen Liebesdiskurs: Flore und Blanscheflur und Apollonius von Tyrland“ - Egidi, Margreth (Schrift und Liebe in der Kultur des Mittelalters (Trends in Medieval Philology 13))

„‚Innenräume‘ des Liebesdiskurses. Spiegelungen des Innen am Beispiel der Gartenmotivik in Minnereden“ - Egidi, Margreth (Innenräume in der Literatur des deutschen Mittelalters. 19. Anglo-German Colloquium Oxford 2005)

Special Section on Individuation during late adolescence and emerging adulthood: German studies (International Journal of Behavioral Development)

Development of a model describing individuated adult child-parent relationships - Buhl, Heike M. (International Journal of Behavioral Development)
This study investigates age-related changes and dyadic-specific differences in adult child–parent relationships. Using an individuation framework, two German samples of 224 and 105 participants aged between 21 and 47 years were administered the Network of Relationships Inventory, the Emotional Autonomy Scale and the Authority Reciprocity Questionnaire. Factor analyses resulted in a measurement model valid for adult children, their mothers and fathers. The model includes connectedness (with emotional and cognitive aspects) as well as individuality (assessed as power symmetry). Connectedness decreased with age. Symmetry in father–child relationships increased over time, while mother–child relationships were perceived to be symmetrical by early adulthood. Child–mother relationships were more connected than child–father relationships. Sons described themselves as more powerful than did daughters.
Keywords: adult child–parent relationships; adulthood; connectedness; Germany; individuation; symmetry

Ein erweitertes individuationstheoretisches Modell zur Vorhersage der aktuellen und geplanten Unterstützung Erwachsener für ihre Eltern - Buhl, Heike M. (Intergenerationelle Transferleistungen in Familien)

Individuation during adolescence and emerging adulthood – Five German studies - Reis, Olaf; Buhl, Heike M. (International Journal of Behavioral Development)
Among theories describing human relationships and interactions, individuation theory has increasingly gained attention over the last three decades. After ideas of individuation were introduced to the USA by German emigrants, such as Erik Erikson and Peter Blos, a second generation of American researchers brought the issue to the fore during the 1980s. Since then, German research has taken up the topic. Current lines of German research resonate with contemporary American research (e.g., Allen, Smetana), but also explore possible extensions of the theory. Here we introduce five German studies that explore relations between individuation and attachment, interactions between transmissions and relationships, or try to extend individuation theory beyond adolescence and the family system.

Significance of individuation in adult child-parent relationships - Buhl, Heike M. (Journal of Family Issues)
This study investigates the significance of adult children's individuation for the adult child—parent relationship. Following Youniss, individuation was assessed via its dimensions of both connectedness and individuality. A sample of 349 participants between 20 and 47 years of age were given questionnaires containing scales from the Network of Relationships Inventory among others. Individuation predicted satisfaction, intimacy, and conflict. The combination of connectedness and individuality did not have any impact on relationship quality. The significance of children's individuation did not differ between young and middle-aged adults.

"Anthropologische Kehre"? Zum Konzept literarischer Weblogs. Erschienen unter der Internet-Adresse: www.turmsegler.net. Juni 2008. Zugleich erschienen - Öhlschläger, Claudia (spatien. zeitschrift für literatur. heft 6: deinesgleichen (2008).)

Hendrik zu Bertrand Marquer, Les Romans de la Salpêtrière. Réceptions d’une scénographie clinique. Jean-Martin Charcot dans l'imaginaire fin-de-siècle - Schlieper, Hendrik (Romanische Forschungen 122.4, 2010)

L’Oiconomie des plaisirs: La praxéologie de l’amour galant: à propos de la „Clélie“ - Steigerwald, Jörn (Zeitschrift für französische Sprache und Literatur 118, 3)